Relationship between organizational culture towards turnover intention among employees in service unit of Malaysia Marine and Heavy Engineering (MMHE) company / Nabilah Atikah Dawan and Nur Adlina Mohamed Nasir - Dawan, Nabilah Atikah; Mohamed Nasir, Nur Adlina (Faculty of Business and Management, 2016)
This research is about a study about the relationship between organizational culture towards the turnover intention in Malaysia Marine and heavy Engineering (MMHE). The organizational culture which including consensual culture, rational culture, developmental culture, hierarchical culture, power distance, uncertainty avoidance, collectivism and masculinity that may affect to the turnover intention among employees. For the purpose of this study, descriptive research was deployed in order to determine the level of organizational culture and also to analyse the most influential factor that affected the employee turnover intention in Malaysian Marine and Heavy Engineering (MMHE). Convenience sampling has been used with 169 respondents as the sample size that has been returned and completed. Questionnaire has been utilized as the survey instrument to gather the data and information about the study. Other than that, data also can be obtained by using two methods that are primary and secondary data such as journal and articles. By using the analysis generated by SPSS (a computerized statistical software) results are analysed and deduction being drawn. The results in data analysis are looked through reliability test, descriptive analysis and Pearson Correlation. Besides, ANOVA Regression model are used for the hypothesis testing. Finally, this finding is perhaps can be contribute and help the management in Malaysian Marine and Heavy Engineering to maintain their employee satisfaction and performance to avoid turnover intention.